A Bank Asya és az OTP Bank Nyrt. összehasonlító elemzése a pénzügyi kimutatások tükrében - Tálos, Lívia; Pavelka, Vivien (Acta Scientiarum Socialium, 2015)
Comparative Analysis of Bank Asya and OTP Bank Plc. in the Light of the Financial Statements.This article aims to compare an Islamic bank, which operates according to religious principles, and a conventional bank. Our study is justified because the global economic crisis has undermined the confidence in Western banks, and as a consequence the eye of the world turned to alternative financial modes. And here they are becoming more involved as a form of alternative financing options.An assessment of a bank performance can be equally important for several economic actors such as shareholders, potential investors, partner banks or clients. The primary sources of analysis are the banks' balance sheets and income statements. They make their decisions according to the information of the statements. For performance analysis, a variety of indicators are available, so it is essential to choose the most representative ones. The indicators most commonly used are that of capital, of liquidity and of earnings. In the light of this we primary use these indicators during our examina-tion.In our study a Turkish bank, named Bank Asya, and the Hungarian OTP Bank was compared. OTP Bank was chosen because it is the largest bank in the banking system in our country (with over 25% market share), and also because it works with the highest interest margin. Bank Asya also holds a significant place in the banking system in Turkey. We would like to emphasize that our study is not representative. The results of comparing the two banks cannot be carried over directly to the comparison of two banking systems. For the latter, a representative macroanalysis would be needed, which will be a further research task.
Keywords: alternative banking and finance models; Islamic banking; comparative performance analysis